2018
DOI: 10.4018/ijcallt.2018070102
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Students' and Teachers' Perceptions of Using the iPad in an Italian English as a Foreign Language Classroom

Abstract: Recent research indicates that mobile technologies can support second language learning. However, studies focused on the use of the iPad and teaching in schools is still scarce. This study reports on an action research project that investigated the use of the iPad in the English as a foreign language (EFL) context in an Italian school. The study sought to investigate learners' and teachers' perceptions of mobile learning through the use of the iPad. The data was collected through a survey (N=41), classroom obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Also, some studies demonstrated how the iOS device helped teachers to provide immediate and personalised feedback on the tasks proposed. For instance, teachers and students reported positively on the use of the builtin iPad messenger app to interact inside and outside the classroom (Morgana & Shrestha, 2018). Mobile devices can have similar characteristics and affordances, but the fact that learners and teachers use the same device with the same applications and the same operating system appeared to facilitate scaffolding, instruction flow and the management of various issues such as app selection or sharing features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, some studies demonstrated how the iOS device helped teachers to provide immediate and personalised feedback on the tasks proposed. For instance, teachers and students reported positively on the use of the builtin iPad messenger app to interact inside and outside the classroom (Morgana & Shrestha, 2018). Mobile devices can have similar characteristics and affordances, but the fact that learners and teachers use the same device with the same applications and the same operating system appeared to facilitate scaffolding, instruction flow and the management of various issues such as app selection or sharing features.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of studies focusing on the use of the iPad in the English as foreign language secondary classroom (e.g., Morgana & Shrestha, 2018;Simpson, Walsh, & Rowsell, 2013). , for example, investigated the effects of using iPads in an Extensive Reading Program on teenage English learners' online activities, reading ability and users' perceptions.…”
Section: Ipads In Secondary Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited research is conducted among participants with other educational backgrounds. Specifically, 2 (12.5%) papers are on secondary or middle school students (Kang & Kim, 2021;Morgana & Shrestha, 2018), and another 2 (12.5%) in other institutions, i.e., the institute of culture and workplace language support (Gasparini, 2018;McLellan et al, 2021), and 1 (6.3%) paper on elementary school students (Pellerin, 2014).…”
Section: Educational and Learning Contextsmentioning
confidence: 99%
“…It is broadly used for political interaction and communication globally and is an essential subject in secondary-school curricula. However, there is a lack of research into the teaching and learning of EFL in secondary education in Italy, where the author is based (Morgana & Shrestha, 2018) and in state education in general (Collins & Muñoz, 2016). This gap was highlighted during the recent COVID-19 pandemic when the situation in many state schools precipitated.…”
Section: Introductionmentioning
confidence: 99%